ANALISIS DAMPAK KONVERSI LAHAN TAMBAK MENJADI SAWAH TERHADAP SOSIAL EKONOMI MASYARAKAT KECAMATAN MATTIRO SOMPE KABUPATEN PINRANG: Analysis of the Socio-Economic Impact of Fish Pond-to-Rice Field Conversion on the Community of Mattiro Sompe Subdistrict, Pinrang Regency - Rahman Ramadhani S; Muhammad Kasnir; Syahrul Djafar (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2026)
Pond farmers in Mattiro Sompe District turned their ponds into rice fields due to a decrease in crop yields, limited seawater availability for saltwater fulfillment in ponds because the estuary experienced siltation which caused ponds far from the estuary to experience. This study aims to identify the factors that affect the conversion of pond land into rice fields and evaluate their impact on the socio-economic conditions of the people of Mattiro Sompe District, Pinrang Regency. Using multiple linear regression analysis with the help of SPSS, it was found that more stable availability of irrigation water and decreased pond productivity were the main drivers of conversion. Economically, people's income increased significantly from an average of Rp8,500,000 to Rp25,855,000 after conversion, with conversion cost as the most influential variable (p = 0.000) and R² value of 0.799. Although there were no statistically significant social variables, land type had the highest contribution to social change (β = 0.316), with an R² of 0.783 indicating the strength of the model. These findings conclude that land conversion has a positive economic impact, but needs to be balanced with attention to social dynamics in the process of adaptation and management of community conflicts.